DIAGNOSTIC ACCURACY OF OCULAR ULTRASOUND IN DETECTION OF RETINAL DETACHMENT: A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2025)
Background: Retinal detachment (RD) is an ophthalmic emergency requiring prompt diagnosis and intervention to prevent permanent vision loss. Ocular ultrasound (OUS), especially point-of-care ultrasound (POCUS), has emerged as a valuable diagnostic tool in cases where direct ophthalmoscopic evaluation is limited or not feasible. Methods: A comprehensive literature search was conducted using databases including PubMed, Google Scholar, Scopus, CINAHL, and LILACS. From 493 initially identified records, 10 studies met the inclusion criteria after screening and duplicate removal. These studies assessed the diagnostic performance of OUS in RD detection using standard statistical measures, typically at a 95% confidence level. Results: The included studies shows the Diagnostic accuracy ranged from 91% to 99.8%, sensitivity from 66.7% to 100%, and specificity from 67.9% to 99%. The PPV and NPV also varied widely, with NPV consistently high (90.1%–100%), indicating a strong ability to rule out RD when ultrasound findings were negative. Six studies reported 100% sensitivity, underscoring the reliability of OUS in emergency and clinical settings. Conclusion: Ocular ultrasound demonstrates high diagnostic accuracy and sensitivity for detecting retinal detachment, supporting its use as an initial diagnostic modality, especially in emergency or resource-limited settings.